Factoring in the forgotten role of renewables in CO2 emission trends using decomposition analysis. (May 2018) - Mohlin, Kristina; Camuzeaux, Jonathan R.; Muller, Adrian; Schneider, Marius; Wagner, Gernot
Abstract: This paper introduces an approach for separately quantifying the contributions from renewables in decomposition analysis. So far, decomposition analyses of the drivers of national CO2 emissions have typically considered the combined energy mix as an explanatory factor without an explicit consideration or separation of renewables. As the cost of renewables continues to decrease, it becomes increasingly relevant to track their role in CO2 emission trends. Index decomposition analysis, in particular, provides a simple approach for doing so using publicly available data. We look to the U.S. as a case study, highlighting differences with the more detailed but also more complex structural decomposition analysis. Between 2007 and 2013, U.S. CO2 emissions decreased by around 10%—a decline not seen since the oil crisis of 1979. Prior analyses have identified the shale gas boom and the economic recession as the main explanatory factors. However, by decomposing the fuel mix effect, we conclude that renewables played an equally important role as natural gas in reducing CO2 emissions between 2007 and 2013: renewables decreased total emissions by 2.3–3.3%, roughly matching the 2.5–3.6% contribution from the shift to natural gas, compared with 0.6–1.5% for nuclear energy. Highlights: An approach for quantifying contributions from renewables in CO2 trends is introduced. The approach is based on decomposition analysis of CO2 emission drivers. US case study: from 2007 to 2013 energy-related CO2 emissions decreased by 10%. Renewables decreased CO2 emissions by 2.3–3.3% matching 2.5–3.6% from natural gas. With cost of renewables decreasing it's important to track their role in CO2 trends.